Adhesive Droplets of Glowworm Snares (Keroplatidae: Arachnocampa spp.) Are a Complex Mix of Organic Compounds - Wolff, Jonas O.; von Byern, Janek; Piorkowski, Dakota; Fang, Jian; Wang, Xungai; Adler, Lewis; Thomas, Donald S.; Hook, James M.; Blamires, Sean J. (Frontiers in Mechanical Engineering, 2021)
Adhesive snares built from silks are fascinating adaptations that have rarely evolved outside spiders. Glowworms (Arachnocampa spp.) are an iconic part of the fauna of Australia and New Zealand that combine the construction of a sticky snare with a bioluminescent lure. Recently, the structure and biomechanical properties of glowworm silk have been studied in detail, but the chemical composition of its adhesive coating, and how it varies between species of Arachnocampa remained unclear, limiting an understanding of the glue function. Here, we studied the chemical composition of the water-soluble fraction of the adhesive droplets from the snares in cave and epigaeic populations of three species of Arachnocampa from mainland Australia, Tasmania, and New Zealand, using a combination of nuclear magnetic resonance and mass spectrometry. We found that glowworm glues comprise a large variety of small organic compounds, with organic acids, amino acids, amino acid derivates, alcohols, urea, and urea derivates being the major fraction, supplemented by small amounts of sugars, fatty acids, and other organic compounds. While there was a general overlap in the compounds detected in the adhesives of all tested Arachnocampa species and populations, the relative amounts differed considerably. We expect that these differences are a product of diet rather than an adaptive response to different environments, but experiments are needed for clarification. The high amount of polar substances and compounds that are hygroscopic at high humidity explains the adhesive properties of the viscous solution and its stability in damp environments. These results contribute to our understanding of the unique prey capture strategy of glowworms. Further, the comparison with convergent spider webs highlights the use of small polar compounds as plasticizers of macro-molecular bioadhesives as a general principle. This may inspire the biomimetic design of novel pressure sensitive adhesives with high performance under high humidity conditions.